2015
DOI: 10.3791/52691
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Human Lymphatic Endothelial Cells by Multi-parameter Fluorescence-activated Cell Sorting

Abstract: Lymphatic system disorders such as primary lymphedema, lymphatic malformations and lymphatic tumors are rare conditions that cause significant morbidity but little is known about their biology. Isolating highly pure human lymphatic endothelial cells (LECs) from diseased and healthy tissue would facilitate studies of the lymphatic endothelium at genetic, molecular and cellular levels. It is anticipated that these investigations may reveal targets for new therapies that may change the clinical management of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The unbound cells were removed into a sterile Falcon tube, pelleted, and resuspended in EGM-2MV supplemented with vascular endothelial growth factor–C before being seeded in fibronectin-coated plastic. For the isolation of the GLA054-LM-LECs, a FACS strategy was applied, as described before (Lokmic et al, 2015), using anti-human podoplanin (Sigma-Aldrich)–Alexa Fluor 488 (1:200; Cell Signaling), Brilliant Violet 421 anti-human CD34 antibody (1:200; BioLegend), PE mouse anti-human CD31 (1:50; Becton Dickinson), and 7AAD PerCP (1:20; BioLegend). For the isolation of GLA061-LM-LECs, a CD31-positive, podoplanin-positive selection strategy was employed using antibody-coated magnetic beads (Dynabeads; Invitrogen, Life Technologies) to separate LECs from other cell types (Osborn et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The unbound cells were removed into a sterile Falcon tube, pelleted, and resuspended in EGM-2MV supplemented with vascular endothelial growth factor–C before being seeded in fibronectin-coated plastic. For the isolation of the GLA054-LM-LECs, a FACS strategy was applied, as described before (Lokmic et al, 2015), using anti-human podoplanin (Sigma-Aldrich)–Alexa Fluor 488 (1:200; Cell Signaling), Brilliant Violet 421 anti-human CD34 antibody (1:200; BioLegend), PE mouse anti-human CD31 (1:50; Becton Dickinson), and 7AAD PerCP (1:20; BioLegend). For the isolation of GLA061-LM-LECs, a CD31-positive, podoplanin-positive selection strategy was employed using antibody-coated magnetic beads (Dynabeads; Invitrogen, Life Technologies) to separate LECs from other cell types (Osborn et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, it has been shown that integration of circulating cells that exhibit lymphendothelial features may initiate a pathologic outgrowth of the lymphatic system. Thus, a third source of tumor LECs comes from transdifferentiation of non-endothelial cells [ 92 ]. Although bone marrow-derived cells (BMDCs), including endothelial progenitor cells, are essential for the formation of new blood vessels, it is conceivable that they may also contribute to neo-lymphangiogenesis in tumors.…”
Section: What Is the Role Of Lymphatic And Blood Endothelial Cells Inmentioning
confidence: 99%
“…Lymphatic ECs lack tight barrier function, and exclusively respond to lymphangiogenic factors, e.g., VEGF-C (4). The availability of protocols for the isolation/purification of ECs from different vascular beds (32) or the lymphatics (54,109) may enable their targeted use in bioengineering different segments of the pulmonary vascular, the bronchial circulation, or the lymphatic tree. A review of the lymphatic endothelium, however, as important as it is for lung function during development (39) and in the mature organ, is beyond the scope of this review.…”
Section: Pulmonary Vascular Organizationmentioning
confidence: 99%